2013
DOI: 10.1111/nhs.12084
|View full text |Cite
|
Sign up to set email alerts
|

Cultural responses to pain in UK children of primary school age: A mixed‐methods study

Abstract: Pain-measurement tools are often criticized for not addressing the influence of culture and ethnicity on pain. This study examined how children who speak English as a primary or additional language discuss pain. Two methods were used in six focus group interviews with 34 children aged 4-7 years: (i) use of drawings from the Pediatric Pain Inventory to capture the language used by children to describe pain; and (ii) observation of the children's placing of pain drawings on red/amber/green paper to denote percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…We noted that the linguistic barriers when reacting to pain might affect verbal expression of the injury. Indeed, children from EAL background provide less elaborate language in their narratives compared to native speakers (Gorman, Fiestas, Peña, & Clark, ; Han, Leichtman, & Wang, ; Parke, ) and also when talking about pain (Azize, Endacott, Cattani, & Humphreys, ; Azize et al., ). For example, Azize et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted that the linguistic barriers when reacting to pain might affect verbal expression of the injury. Indeed, children from EAL background provide less elaborate language in their narratives compared to native speakers (Gorman, Fiestas, Peña, & Clark, ; Han, Leichtman, & Wang, ; Parke, ) and also when talking about pain (Azize, Endacott, Cattani, & Humphreys, ; Azize et al., ). For example, Azize et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Azize et al. () found that EAL children tended to focus their stories either on using limited vocabulary (albeit very animated) or providing extended narratives which were storying their experiences of pain to a far greater extent than monolingual children.…”
Section: Discussionmentioning
confidence: 99%
“…Vocabulary to describe pain (Azize, Endacott, Cattani, & Humphreys, 2013;Franck, Noble, & Liossi, 2010;Johnson et al, 2016); 2. Vocabulary to direct the actions of others in response to the pain or injury (Azize et al, 2013;Ely, 1992); 3. Vocabulary to describe the location of the pain (Ely, 1992;Franck et al, 2010); 4.…”
Section: Discussionmentioning
confidence: 99%
“…36,43 Örneğin; beyaz ırkın ağırlıklı olduğu toplumda yaşayan ve ikinci dilini konuşan siyahi Afrikalı Amerikalı çocuklar, Avrupalı Amerikalı çocuklardan daha az sözsel ifadeler kullanarak ağrılarını ifade etmektedirler. 36 Benzer şekilde, İngiltere'de yaşa-yan ve İngilizceyi ikinci dil olarak kullanan Arap ve Kürt çocukların, ağrıyı tarif etmek için İngiliz kökenli çocuklardan daha fazla zaman harcadıkları görülmüştür.…”
Section: Kültürel Etmenleri̇n Ağri Davranişlari İfade Ve Başa çIkma Yunclassified
“…36 Benzer şekilde, İngiltere'de yaşa-yan ve İngilizceyi ikinci dil olarak kullanan Arap ve Kürt çocukların, ağrıyı tarif etmek için İngiliz kökenli çocuklardan daha fazla zaman harcadıkları görülmüştür. 43 Elde edilen kanıtlar, ülkelerde azın-lık grup olan toplumların yetersiz şekilde ağrı tedavisi aldıkları bulgusunu desteklemektedir. Mesela, Jimenez ve ark.nın çalışmasında; İspan-yolca konuşan Latin kökenli çocuklar ile İngilizce konuşan Amerikalı Kafkas çocuklarla aynı seviyede ağrı öz bildirimi yapılmış, fakat Latin çocuklar %30 daha az analjezik tedavisi almışlardır.…”
Section: Kültürel Etmenleri̇n Ağri Davranişlari İfade Ve Başa çIkma Yunclassified